2020
DOI: 10.1111/pcmr.12854
|View full text |Cite
|
Sign up to set email alerts
|

IMP dehydrogenase rod/ring structures in acral melanomas

Abstract: Acral lentiginous melanoma (ALM) is a rare subtype of melanoma with aggressive behavior. IMPDH enzyme, involved in de novo GTP biosynthesis, has been reported to assemble into large filamentary structures called rods/rings (RR) or cytoophidium (cellular snakes). RR assembly induces a hyperactive state in IMPDH, usually to supply a high demand for GTP nucleotides, such as in highly proliferative cells. We investigate whether aggressive melanoma tumor cells present IMPDH‐based RR structures. Forty‐five ALM paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Thereafter, many other conditions have been shown to promote IMPDH cytoophidium assembly, such as glutamine deficiency, disturbance of one-carbon pathway and treatment by a variety of clinical drugs, implying that cytoophidium formation is correlated with changes in the metabolic state of the cell (Calise et al, 2014;Calise et al, 2016;Keppeke et al, 2016). Yet, the IMPDH cytoophidium is also observed in certain cells and tissues without additional stimulus, such as mouse pluripotent stem cells, antigen-activated T lymphocytes, retinal photoreceptor cells, and some tumors, such as acral melanomas and clear cell renal cell carcinoma (Calise et al, 2018;Duong-Ly et al, 2018;Keppeke et al, 2020;Keppeke et al, 2018;Plana-Bonamaiso et al, 2020;Ruan et al, 2020).…”
Section: / 29mentioning
confidence: 99%
“…Thereafter, many other conditions have been shown to promote IMPDH cytoophidium assembly, such as glutamine deficiency, disturbance of one-carbon pathway and treatment by a variety of clinical drugs, implying that cytoophidium formation is correlated with changes in the metabolic state of the cell (Calise et al, 2014;Calise et al, 2016;Keppeke et al, 2016). Yet, the IMPDH cytoophidium is also observed in certain cells and tissues without additional stimulus, such as mouse pluripotent stem cells, antigen-activated T lymphocytes, retinal photoreceptor cells, and some tumors, such as acral melanomas and clear cell renal cell carcinoma (Calise et al, 2018;Duong-Ly et al, 2018;Keppeke et al, 2020;Keppeke et al, 2018;Plana-Bonamaiso et al, 2020;Ruan et al, 2020).…”
Section: / 29mentioning
confidence: 99%
“…Keppeke et al reported a high frequency (91.0%) in 45 acral lentiginous melanoma paraffin-embedded tissue samples and a frequency (39.0%) in 59 melanocytic nevi samples. [ 2 ] In line with these data, Covini et al reported that ant-RR structures had been detected in 15 out of 75 (20%) chronic HCV infection patients. [ 22 ] Stinton et al reported a frequency (4.8%) in 315 chronic HCV infection patients.…”
Section: Discussionmentioning
confidence: 71%
“…A recent study has shown that cytidine triphosphate synthase (CTPS), which catalyzes the rate-limiting step in the de novo CTP synthetic pathway in which UTP is converted into CTP, also assembles into RR structures ( 53 ). All of them provide a possibility that screening for the presence of the RR pattern can be used to analyze the metabolic status and prognosis of tumors ( 54 ). Unfortunately, we did not observe whether RR pattern is related to tumors in our study, which may be because our clinical data are not detailed enough.…”
Section: Discussionmentioning
confidence: 99%